Keterkaitan Antara Administrasi Pendidikan dan Supervisi Pembelajaran dalam Meningkatkan Profesionalisme Guru - Qonita, Qonita; Mutia Rahmah; Fatimah Az-Zahra; Muhammad Iqbal (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
Educational administration, learning supervision, and teacher professionalism are crucial components in efforts to improve the quality of education. However, supervision practices in schools do not focus on developing teacher competencies. This creates a mismatch between the implementation of supervision and the ideal concept of supervision, which should be developmental, dialogical, and sustainable. This study aims to develop a more effective supervision model and to improve teacher professionalism. The method used is a descriptive-conceptual analysis of learning supervision practices, teacher needs, and modern supervision principles. The study results in the Pro-Guru (Continuous Professional Supervision of Teachers) model, which includes participatory planning, supervision implementation using a variety of techniques, data-based evaluation, and follow-up through training and professional mentoring. The implications of this model are the creation of a more humanistic and structured supervision process that can foster a culture of professionalism and innovative learning in schools.